PENERAPAN BAURAN PEMASARAN DAN POLITICAL WILL PEMERINTAH PADA INDUSTRI BATIK BOMBA DI KOTA PALU - Suriyani, Suriyani (Katalogis, 2017)
The aims of this study are: to define and analyze marketing mix implemented in bomba batik industry in Palu city, to define and analyze the government political will on bomba batik industry in Palu City, and explore constraints and supporting factors on the implementation of marketing mix by batik bomba entrepreneurs and political will of the local government. The result of this research shows that: 1) marketing mix strategy that include product, price, place, and promotion, has been known and implemented by the batik bomba entrepreneurs in Palu City; 2) political will of the government has been well implemented and is an important factor in the development of batik bomba industry in Palu City.